OWE-21 Seronegative villous atrophy of unknown origin displays distinctive clinical and genetic features and natural history. Issue 2 (June 2019) - Schiepatti, Annalisa; Sanders, David S; Goodwin, John; Key, Tim; Giuffrida, Paolo; Silvestri, Annalisa De; Biagi, Federico
Abstract : Introduction: Seronegative villous atrophies of unknown origin (SNVA-UO) are rare and poorly defined. Aims: i) To classify SNVA-UO and study their clinical features, histology, HLA and natural history. ii) To compare genetics and survival between SNVA-UO and patients affected by coeliac disease (CD) and complicated CD. Methods: Notes of SNVA-UO patients from two referral centres were retrospectively reviewed and data on follow-up prospectively collected until 01/2019. CD and its complications and other causes of SNVA (autoimmune enteropathy, common variable immunodeficiency, olmesartan enteropathy, parasites, etc) were thoroughly excluded. Evidence of lymphoproliferative features (TCR-γ clonality on duodenal biopsies and/or past history of extra-intestinal lymphoproliferative disorders) and persistent villous atrophy (VA) during follow-up were used as criteria to classify them, as follows. GROUP 1: SNVA without lymphoproliferative features and with spontaneous recovery of VA. GROUP 2: persistent SNVA without lymphoproliferative features. GROUP 3: persistent SNVA with lymphoproliferative features. HLA DQA1 and DQB1 allelic frequencies were compared using χ2 test and Fisher test. Survival was analysed by means of Kaplan-Meier curves. Results: 76 patients with SNVA-UO were enrolled. 50 were included in group 1 (26F, age at diagnosis 49±18 years), 14 in group 2 (7F, 43±14), 12 in group 3 (5F, 52±17). VA spontaneously normalized in 47 patients in group 1 after a median of 10 months, IQR 5–14.5. Histological response occurred in 4 patients in group 2 on traditional immunosuppressants. Survival analysis showed significant differences (p<0.001), with group 2 characterised by long-term survival (100% alive, median follow-up 61 months, IQR 50.5–97.5) and group 3 by the poorest prognosis and a mortality higher than complicated CD (58% of patients dead after a median of 11 months from diagnosis, IQR 9.5–40). Group 1 displayed a favourable outcome similar to CD. Group 2 shows a high frequency of HLA-DQB1*0301 and DQB1*06, while HLA-DQB1*02 was more frequent in group 3 and in group 1. Partial VA, dyspepsia and absence of weight loss predicted inclusion into group 1 (p<0.001), while hypoalbuminemia (<3.5 g/dL) inclusion into group 3 (p<0.02). Conclusions: For the first time we demonstrated that SNVA-UO is made by heterogeneous enteropathies with distinct clinical features, genetics and prognosis. Clinical management should be tailored accordingly.